Keeping the balance in NAD metabolism. (9th January 2019) - Strømland, Øyvind; Niere, Marc; Nikiforov, Andrey A.; VanLinden, Magali R.; Heiland, Ines; Ziegler, Mathias
Abstract : Research over the last few decades has extended our understanding of nicotinamide adenine dinucleotide (NAD) from a vital redox carrier to an important signalling molecule that is involved in the regulation of a multitude of fundamental cellular processes. This includes DNA repair, cell cycle regulation, gene expression and calcium signalling, in which NAD is a substrate for several families of regulatory proteins, such as sirtuins and ADP-ribosyltransferases. At the molecular level, NAD-dependent signalling events differ from hydride transfer by cleavage of the dinucleotide into an ADP-ribosyl moiety and nicotinamide. Therefore, non-redox functions of NAD require continuous biosynthesis of the dinucleotide. Maintenance of cellular NAD levels is mainly achieved by nicotinamide salvage, yet a variety of other precursors can be used to sustain cellular NAD levels via different biosynthetic routes. Biosynthesis and consumption of NAD are compartmentalised at the subcellular level, and currently little is known about the generation and role of some of these subcellular NAD pools. Impaired biosynthesis or increased NAD consumption is deleterious and associated with ageing and several pathologies. Insults to neurons lead to depletion of axonal NAD and rapid degeneration, partial rescue can be achieved pharmacologically by administration of specific NAD precursors. Restoring NAD levels by stimulating biosynthesis or through supplementation with precursors also produces beneficial therapeutic effects in several disease models. In this review, we will briefly discuss the most recent achievements and the challenges ahead in this diverse research field.